2015
DOI: 10.1001/jamapediatrics.2015.0636
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Nutritional Treatment for Preschool-Aged Children With Cystic Fibrosis

Abstract: IMPORTANCE Evidence-based treatments that achieve optimal energy intake and improve growth in preschool-aged children with cystic fibrosis (CF) are a critical need. OBJECTIVE To test whether behavioral and nutritional treatment (intervention) was superior to an education and attention control treatment in increasing energy intake, weight z (WAZ) score, and height z (HAZ) score. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial included 78 children aged 2 to 6 years (mean age, 3.8 years) with CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
2
32
0
3
Order By: Relevance
“…The overall birth prevalence of CF in Washington State can be calculated based on vital statistics data; between 2006 and 2013, there were 702,670 live births in Washington State (17), giving an estimated birth prevalence of CF of 1 per 5,128 live births. The birth prevalence in the overall period, 1996-2013, should not have differed substantially from the prevalence in the sub-cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall birth prevalence of CF in Washington State can be calculated based on vital statistics data; between 2006 and 2013, there were 702,670 live births in Washington State (17), giving an estimated birth prevalence of CF of 1 per 5,128 live births. The birth prevalence in the overall period, 1996-2013, should not have differed substantially from the prevalence in the sub-cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2006, newborn screening for CF has been mandated in Washington State, and nearly all infants with CF are diagnosed within weeks of delivery. Poor neonatal outcomes could be a harbinger of more severe disease in infants with CF, and when infants are diagnosed through screening, these adverse neonatal outcomes may identify infants that need earlier and more aggressive nutritional interventions (16, 17) or targeted CF therapies (18, 19). …”
mentioning
confidence: 99%
“…10, [136][137][138][139] In multiple studies, families consistently reported challenges with mealtime energy-intake goals due to demanding mealtime behaviors, leading to significant stress. 8, 9, 124-127 These mealtime behavioral challenges can predict calorie intake and weight gain.…”
Section: Behaviormentioning
confidence: 99%
“…1,2,4,11 The CFF recommends that these children consume 110% to 200% of the energy intake requirement for healthy peers and eat at least 3 meals and 3 snacks per day to achieve this elevated intake. [3][4][5] Using electronic monitors, participants' adherence was estimated at 42% (2.5 bottle openings) at home and 94% (0.9 bottle opening) at school.…”
Section: Figurementioning
confidence: 99%
“…3,7,8 Adherence to pancreatic enzyme regimens is also low, ranging from 27% to 46%. 9 Although effective behavioral interventions have been developed to improve nutritional outcomes in young children, 10,11 less is known about adherence to pancreatic enzyme therapy.…”
mentioning
confidence: 99%